Phonon and Raman scattering of two-dimensional transition metal dichalcogenides from monolayer, multilayer to bulk material1. (7th May 2015) - Zhang, Xin; Qiao, Xiao-Fen; Shi, Wei; Wu, Jiang-Bin; Jiang, De-Sheng; Tan, Ping-Heng
<x xml:space="preserve">Abstract</x> This review focuses on the basic properties and potential applications of Raman spectroscopy of two-dimensional transition metal dichalcogenides from monolayer, multilayer to bulk materials.